Raltegravir Attenuates Experimental Pulmonary Fibrosis In Vitro and In Vivo - Xue Zhang; Haidi Huang; Guanghua Zhang; Defang Li; Hongbo Wang; Wanglin Jiang (Frontiers Media S.A., 2019)
Raltegravir, an inhibitor of human immunodeficiency virus-1 (HIV-1) integrase, has been used to treat HIV/acquired immunodeficiency syndrome; however, its therapeutic effects on pulmonary fibrosis have not been investigated. In this study, the in vitro effects of raltegravir (RAV) on transforming growth factor beta 1 (TGF-β1)-induced pulmonary fibrosis on L929 mouse fibroblasts were investigated. In addition, the effects of RAV on an in vivo pulmonary fibrosis model induced by intratracheal instillation of bleomycin were investigated. The proliferation of L929 cells was inhibited after RAV treatment. Meanwhile, the in vitro and in vivo protein expression of nucleotide-binding oligomerization domain-like receptor 3 (NLRP3), high-mobility group box 1 (HMGB1), toll-like receptor 4 (TLR4), prolyl hydroxylase domain protein 2, phosphorylated nuclear factor-κB (p-NF-κB), hypoxia-inducible factor-1α (HIF-1α), collagens I and III was reduced relative to TGF-β1 or the bleomycin group. Raltegravir ameliorated pulmonary fibrosis by reducing the pathology score, collagen deposition, and expression of α-smooth muscle actin, NLRP3, HMGB1, TLR4, inhibitor of kappa B, p-NF-κB, HIF-1α, collagen I, and collagen III. The results of this study demonstrate that RAV attenuated experimental attenuates pulmonary fibrosis by inhibiting NLRP3 activation.